Information and Communication Technology Use by Reproductive Health Workers in Nigeria: State of the Art, Issues and Challenges - Olatokun, Wole; Adeboyejo, Olufunke (Human Technology, 2009)
This study investigated reproductive health workers' (RHWs) use of ICTs, the effects of ICTs on their job functions, and the challenges limiting full exploitation of ICTs. The study adopted a descriptive survey design. Stratified sampling technique was used to select a sample of 360 RHWs of the University College Hospital, Nigeria. A questionnaire obtained the data, and frequencies and percentage distributions were the analytical techniques adopted. Findings revealed that RHWs indicated extensive use of ICTs in their job functions. Faster access to relevant medical information, easy exchange of information with colleagues, and increased efficiency were the major impacts of ICT usage on their activities. The information accessed through ICTs was primarily educational, health, and research. Findings equally revealed that the major challenges in ICT use were erratic power supply and inadequate access to ICT facilities. Based on the findings, recommendations were made towards enhancing better utilization of ICTs by RHWs.